Serotherapy as Graft-Versus-Host Disease Prophylaxis in Haematopoietic Stem Cell Transplantation for Acute Lymphoblastic Leukaemia - Keogh, Steven J.; Dalle, Jean-Hugues; Admiraal, Rick; Pulsipher, Michael A. (Frontiers in Pediatrics, 2022)
Serotherapy comprising agents such as anti-thymocyte globulin and the anti-CD52 monoclonal antibody alemtuzumab is used widely to reduce the incidence of graft-versus-host disease (GvHD) after paediatric haematopoietic stem cell transplantation (HSCT). The outcome of transplants using matched unrelated donors now approaches that of matched sibling donors. This is likely due to better disease control in recipients, the use of donors more closely human-leukocyte antigen (HLA)-matched to recipients, and more effective graft-versus-host disease (GvHD) prophylaxis. The price paid for reduced GvHD is slower immune reconstitution of T cells and thus more infections. This has led to studies looking to optimize the amount of serotherapy used. The balance between prevention of GvHD on one side and prevention of infections and relapse on the other side is quite delicate. Serotherapy is given with chemotherapy-/radiotherapy prior to HSCT. Due to their long half-lives, agents used for serotherapy may be detectable in patients well after graft infusion. This exposes the graft-infused T cells to a lympholytic effect, impacting T-cell recovery. Excessive serotherapy may lead to no GvHD but a higher incidence of infections and relapse of leukaemia, while under-dosing may result in a higher chance of serious GvHD as immunity recovers more quickly. Individualized dosing is being developed through studies including retrospective analyses of serotherapy exposure, population pharmacokinetic modelling, therapeutic drug monitoring in certain centres, and the development of dosing models reliant on factors including the patient’s peripheral blood lymphocyte count. Early results of “optimal” dosing strategies for serotherapy show promise of improved overall survival.